Respon Temu Putih dan Temu Mangga dengan Pemberian BA dan 2,4-D secara In Vitro - Muhammad Isra’ Aulia; Rustikawati; Entang Inoriah (GEMA AGRO, 2020)
Calus and shoot induction of curcuma sp requires the balance amount of auxin and cytokinine which are suitable for the plant species. This study was aimed at evaluating the response of ‘temu putih’ (Curcuma zedoaria Rosc.) and ‘temu mangga’ (Curcuma mangga Val.) to the supplementation of 5 ppm BA and several levels of 2,4-D on the MS medium of in vitro culture. The study was conducted in the Laboratory of Agronomy, Department of Agriculture, Faculty of Agriculture, the University of Bengkulu, from December 2018 to February 2019. The plant material was explans isolated from the buds of curcuma tubers. The experiment was conducted in a completely randomized design arranged in factorial with 2 factors. The first factor was the kinds of curcuma i.e . C. zedoaria and C.mangga. The second factor was the concentration of 2,4–D i.e. 0 ppm, 1 ppm and 2 ppm. The base culture medium was MS with 5 ppm BA. The experimental unit consisted of three botle each of which containing of 1 explant. The treatment was repeated three times amounting to 54 experimental units. The results indicated that both curcuma had different growth respon to in vitro culture. Addition of 2,4-D to the MS medium containing 5 ppm BA produced cally. Callus induction was formed in in vitro culture of Curcuma zeodiaria suplemented with 1 ppm 2,4-D. Up to 2 ppm of 2,4-D, cally production of Curcuma mangga still increasing. Addition of 5 ppm of BA 5 to MS medium induced shoot formation in Curcuma zeodiaria but not in Curcuma mangga.